A multiscale projection approach for the coupled global–local structural analysis of photovoltaic modules. (15th December 2016) - Aßmus, M.; Naumenko, K.; Altenbach, H.
Abstract: The present contribution deals with the modeling and computational simulation of photovoltaic modules in the context of structural mechanics. Thereby, the focus is on the division of the boundary value problem of linear elastomechanics into two characteristic scales. The multiscale modeling starts at the global scale by means of an eXtended LayerWise Theory for a symmetric three-layered composite structure. A specially developed finite element is used to realise the discretisation. For the local structural analysis, a three dimensional unit cell is introduced which is representative in both plane directions and represents the structure of a photovoltaic module in transverse direction completely. The coupling of these two scales is carried out by the projection of the global deformations on the boundaries of the local structure, while the focus is on the transition from composite structure to three dimensional continuum. Thereby, characteristic coordinates for the location of a solar cell and an exemplary loading scenario are considered. Overall, a modeling and simulation approach is presented which permits a numerically efficient solution of structure–mechanical problems on photovoltaic modules through a sequential procedure of a deductive multiscale approach.